👤

Qui peux m'aider à résoudre l'équation merci bonne journée
-2x² +6x-4=0
(x-1)²+(5-3x)(x-1)=0


Répondre :

-2x² +6x-4=0

 -2x² + 6x − 4 = 0     avec    a = -2 , b = 6 et c = -4

Δ = b² − 4ac 

Δ= (6)² − 4×-2×-4 

Δ= 4

Δ > 0 alors l'équation -2x² + 6x − 4 = 0 admet 2 solutions réelles x1 et x2

or  √4 = 2

x1 = (-b − √Δ)/2a 

x1= (-6 − 2) / -4 

x1= 2  

x2 = (-b + √Δ)/2a 

x2= (-6 + 2) / -4 

-2x² + 6x − 4 comme factorisation : -2(x − 2)(x − 1)

Donc S = [1 ; 2]

(x-1)²+(5-3x)(x-1)=0
(x-1)[(x-1)+(5-3x)]
(x-1)(-2x+4)
x-1=0      ou -2x+4=0
x=1              -2x=-4
                       x=2   S= [-4 ; 1 ]